"My faith in the constitution is whole" : Barbara Jordan and the politics of scriptures - Owens, Robin L. (Race, religion, and politics, 2022)
"This is a critical investigation of the engagements of scriptures in the life and speeches of U.S. Congresswoman Barbara C. Jordan (1936-1996). This study explains how scriptures work and are used by Barbara Jordan as a vehicle for political activism to illustrate an example of a larger phenomenon of scripturalizing and scripturalization outside of the context of institutional religion. In order to give a fuller context to Barbara Jordan's rhetorical strategies as an African American woman, Owens first considers the lives, speeches and use of scriptures of the formidable 19th century African American women orators and political activists, Maria W. Stewart and Anna Julia Cooper, who serve as precursors to Barbara Jordan. The author argues that Barbara Jordan makes American scripture, i.e., the Constitution, function in her speeches as a central component in a discursive rhetorical strategy of indirection, which she refers to as "signifying on scriptures." Jordan uses the Constitution, along with her personal history as an African American woman, to promote advocacy for racial justice and gender equality. The book is proposed for a new series, edited by Terrence Johnson, on Race, Religion, and Politics. Race, Religion, and Politics explores the increasingly creative and critical attention paid by scholars in recent decades to race and racial construction-political, cultural, theological, and philosophical-in the formation of religion and in the relationship between religion and politics. This book series examines the conditions under which religion and politics coexist within varying and competing conceptual schemes of race. The books in the series will engage with new narratives emerging from the study of global capitalism and from public discourse on democracy, social transformation, and democratic theory. Broadly historical and theological, the series showcases work that creatively weaves together methods and critical insights from a range of disciplines and debates. It seeks to uncover, examine, and inform global discussions on the most pressing issues emerging from religion and politics, race and religion, and faith and social transformation"--